Clima organizacional: estudo de caso em uma empresa prestadora de serviços no setor aéreo - Silva, Jeovane Cruz da (Brasil, 2024)
This study deals with an organizational climate research in a service provider company in the aviation sector. The general objective is to assess the level of organizational climate at MSC Airport Services – Parintins Base and specific objectives include: identifying factors influencing organizational climate quality; evaluating the positive and negative aspects of organizational climate; proposing actions to improve organizational climate. The methodology follows a quantitative-qualitative approach, with technical procedures including documentary review and field research; data collection instruments encompass documentary sources, questionnaires, and observations; data analysis technique involved content analysis, with ten employees from the company as research subjects. Factors influencing organizational climate quality were revealed to include well-being, teamwork spirit, autonomy, work-life balance, leadership, and collaborative communication. However, negative aspects such as inadequate infrastructure, interpersonal relationship difficulties, ineffective interdepartmental communication, unsatisfactory remuneration, and limited professional growth opportunities were identified. Therefore, it is imperative to adopt measures to enhance organizational climate and promote an environment of appreciation, motivation, and commitment to the organization.